Kontribusi Industri Tenun Pringgasela terhadap Ekonomi Masyarakat Lombok Timur - Husnul Padhli Al Idrus (YASIN, 2026)
The Pringgasela weaving industry constitutes both a cultural heritage and a source of livelihood for the local community. However, previous studies have tended to examine marketing, tourism, women’s empowerment, and craft sustainability separately, leaving its economic contribution as a local ecosystem insufficiently explained in an integrated manner. This study aimed to analyze the contribution of the Pringgasela weaving industry to the economy of the East Lombok community and to identify the supporting and inhibiting factors affecting its sustainability. The study employed a descriptive qualitative approach conducted in Pringgasela Village. Data were collected through observation, semi-structured interviews with actors involved in weaving production and development, and documentation, and were subsequently analyzed through the stages of data reduction, data presentation, and conclusion drawing and verification. The results showed that the weaving industry contributed as both a primary and supplementary source of income, created household-based employment opportunities, expanded women’s economic participation, encouraged product diversification among micro, small, and medium enterprises, and connected craft production with cultural tourism. However, the sustainability of these contributions remained constrained by limited market access, competition with mass-produced textiles, uneven adoption of digital marketing, and weak artisan regeneration. This study concluded that the economic sustainability of the Pringgasela weaving industry requires stronger business institutions, cultural identity-based product innovation, optimized digital marketing, a more equitable distribution of added value, and greater youth involvement. These findings contribute to the development of studies on culture-based local economies and provide practical implications for governments, business actors, and communities in strengthening the weaving industry ecosystem sustainably.